2004
DOI: 10.1073/pnas.0308512100
|View full text |Cite
|
Sign up to set email alerts
|

Incipient Alzheimer's disease: Microarray correlation analyses reveal major transcriptional and tumor suppressor responses

Abstract: The pathogenesis of incipient Alzheimer's disease (AD) has been resistant to analysis because of the complexity of AD and the overlap of its early-stage markers with normal aging. Gene microarrays provide new tools for addressing complexity because they allow overviews of the simultaneous activity of multiple cellular pathways. However, microarray data interpretation is often hindered by low statistical power, high false positives or false negatives, and by uncertain relevance to functional endpoints. Here, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

70
870
4
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 943 publications
(946 citation statements)
references
References 78 publications
70
870
4
2
Order By: Relevance
“…The abnormality of the complement system has been reported in brain injury and neurodegenerative disease (D'Ambrosio et al 2001;Gasque 2004), including AD. In the brain of AD patient, it has been observed that the expression of C1q, C3b, C4d and C5b-9 is elevated, and the MAC colocalizes with senile plaques and tangle-positive neurons (Blalock et al 2004;Fonseca et al 2004;Katsel et al 2009;Shen et al 2001). In addition, in the microvasculature, microglia are reported to surround the fibrillar Ab deposits (Fan et al 2007).…”
Section: Neuronmentioning
confidence: 99%
“…The abnormality of the complement system has been reported in brain injury and neurodegenerative disease (D'Ambrosio et al 2001;Gasque 2004), including AD. In the brain of AD patient, it has been observed that the expression of C1q, C3b, C4d and C5b-9 is elevated, and the MAC colocalizes with senile plaques and tangle-positive neurons (Blalock et al 2004;Fonseca et al 2004;Katsel et al 2009;Shen et al 2001). In addition, in the microvasculature, microglia are reported to surround the fibrillar Ab deposits (Fan et al 2007).…”
Section: Neuronmentioning
confidence: 99%
“…The significance level was set at a false discovery rate (FDR) of 0.2, 20 which is reasonably robust as an exploratory microarray study for differential expression analysis 21,22 as well as correlation analysis. 23 Moreover, the functional annotation may increase the robustness by providing evidence of significant overrepresentation of a group of genes from the same biological process. [23][24][25] Correlation analysis between protein levels and cytoarchitectural traits Protein levels of protein kinase B (Akt), neuronspecific enolase (ENO2), cyclin-dependent kinase 5 (CDK5), glial fibrillary acidic protein (GFAP), (StatView).…”
Section: Microarray Datamentioning
confidence: 99%
“…23,24 However, although promising, the clear difficulties in obtaining brain tissue and the fragile nature of isolated RNA render transcriptome studies quite difficult. 25,26 Microarray analysis, widely used for ND and neuropsychiatric disorders, provided much information about the transcriptional profiles in pathological states, [27][28][29] although discordant results have been often reported. The lack of convergence could be attributed to microarray drawbacks (discussed in 8,9,15 ), as well as to the variable quality/integrity of RNAs strictly influenced by pH, 25 which may dramatically alter the binding to the nucleotide probes, affecting the measure of gene expression levels.…”
Section: Introductionmentioning
confidence: 99%